How Important Risk Management Culture in Local Governments? - Resha Dwi Ayu Pangesti Mulyono (Universitas Muhammadiyah Yogyakarta, 2020)
The aim of this study is how important to develop risk management culture in Local Government. This research uses a case study approach with an exploratory study, then the steps taken by the researcher to analyze interview data by (a) informal conversation interviews, (b) approaches using interview general guidelines, and (c) open standard interviews. The results of the interviews were recorded with a recording aid and then processed with NVIVO software then analyzed and the conclusions drawn from the interviews. The Results of this research are the important thing from risk management culture in Local Government for Creating value, an integral part of organizational processes, part of decision making, and explicitly discussing uncertainty for Good Governance.